Pelatihan Internet Sehat dan Aman bagi Siswa SMK Masmur Pekanbaru - Guntoro Guntoro; Lisnawita Lisnawita; Muhamad Sadar (Jurnal Pengabdian Pada Masyarakat, 2019)
TRAINING OF HEALTHY AND SAFE INTERNET FOR STUDENTS OF MASMUR VOCATIONAL SCHOOL, PEKANBARU. Internet technology is a tool that can be used by the younger generation to do creativity and innovation. The internet can be used to find information, pictures, entertainment, music, and lessons. Besides the internet has a positive impact, the internet also has a negative side, including sexual harassment, pornography, online game addiction, and violence. The method of implementing this service is distributing questionnaires before giving material, giving material about the whole internet, demonstrating useful internet applications, distributing questionnaires after giving material, distributing leaflets about healthy internet and evaluating the implementation of service activities. The results of this service activity are (1) the suitable internet training has been carried out by the desired target, and the training participants get motivation, knowledge, and insights about ICT and use of the internet healthily and safely. (2) Knowing information about the impact of internet use both from the positive and negative sides. (3) Students of Pekanbaru Masmur Vocational School can develop self-skills through the internet. (4) With the existence of proper internet training, it is expected to avoid the dangers of the internet from the negative side. (5) Find out tips on how to surf healthily and safely. (6) Based on the evaluation, participants understand the material that has been delivered and agree to the use of healthy and safe internet.